SOCIAL ACTIVITY IN THE PUBLIC AREA OF SALMAN MOSQUE ITB AND ITS EFFECTS TOWARD LAYOUT - Febriani Eka Puteri (Jurnal Sosioteknologi, 2016)
The function of the mosque grows continuously, as consequences of human activities that are always followed by other activities afterwards. The Increasing number of users and the type of activities effecting the needs for more area for the mosque to grow. This resulted in an imbalance between user behavior in activity and the mosque physical environment. Therefore, the results of the architectural design could be one of the behaviors facilitator, but it also could be a drawback of the behavior. Salman Mosque has been chosen for the research because of its long history, aged over 50 years, and a first mosque located on campus with lively activity. This research aims to asses the Salman Mosque accommodation of the user need to what extent and to observe the tendency of the current user behavior pattern. The method used is a combination of qualitative methods in the initial survey, conducted by distributing questionnaires to determine what will be raised in the research, and ethnographic. As well as qualitative methods to understand the concept of Salman Mosque interior, facilities, situations, and behaviors. The result of this research is concluded that Salman Mosque has fulfilled the activity needs, however, the capacity of the mosque has not been able to accommodate the number of users at the busiest time. The physical state of the mosque has an impact on the behavior of the user, such as complying the flow of circulation in accordance to the space organization, such as gathering in an open area that has better air circulation. That kind of behavior is making influence on the environment itself, for instance its addition on the facility outside the original concept of the mosque. Hereby, it is expected to give benefits for being consideration in the development of Salman Mosque, and to be a reference for further research.Keywords : layout, social activity, Salman mosque